When Prosperity is Not Shared : The Weak Links between Growth and Equity in the Dominican Republic - World Bank (Washington, DC, 2014)
The Dominican Republic has low economic mobility, with less than 2 percent of its people climbing to a higher income group during the decade, compared to an average 41 percent in the Latin America and Caribbean region as a whole. Despite improving access to basic goods and services such as water and education, coverage and quality remain uneven, thus limiting the economic opportunities of many disadvantaged people. This reflects their inability to influence the system to their benefit, a manifestation of weak political agency. This report uses a comprehensive definition of "equity" which entails that citizens must have equal access to opportunities, be able to live in dignity, and have the autonomy and voice to participate fully in their communities and decide on life plans that they have reason to value. This report identifies three broad goals for addressing the underlying causes of economic inequity in the Dominican Republic: (1) promote equitable, efficient, and sustainable fiscal policy; (2) build fair, transparent, and efficient institutions that will improve the provision and quality of public goods and services, expand economic opportunities, increase upward mobility, and better protect economically vulnerable Dominicans; and (3) strengthen access of the poor to labor markets and increase the demand for their labor, so as to make efficient use of human capital and allow the poor to benefit from economic growth. The analysis presented in this study analyzes mobility within generations by measuring directional income movement, that is, the net upward or downward movement in individual incomes over time. Serious analytical efforts should be devoted to understanding the apparent disconnection between macro and micro data that hinders the ability of national statistics to accurately reflect macroeconomic and social progress.